2017
DOI: 10.12693/aphyspola.132.1556
|View full text |Cite
|
Sign up to set email alerts
|

Human Tissue Investigations Using PALS Technique - Free Radicals Influence

Abstract: The positron annihilation lifetime spectroscopy was applied to the samples of the human uterine leiomyomas and the normal myometrium tissues taken from the selected place of the uterus during a surgery. The method indicated differences in values of the measured positron annihilation lifetime spectroscopy parameters (lifetimes and intensities) between healthy and diseased tissue samples. The additional measurements were performed either in darkness or in presence of visible light which influenced the free radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…In the body, the mean lifetime of ortho-positronium varies from approximately 1.8 ns in pure water to approximately 4 ns in human skin. 80 Moreover, both formation probability and mean lifetime depend on the concentration of the bio-fluids and bio-active molecules 81,82 and the mean lifetime can be established in the human body with the precision of approximately 20 ps. 29 There are investigations demonstrating differences between normal and cancerous cells with changes of the positronium lifetime during dynamic processes undergoing in model and living biological systems.…”
Section: Positronium Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the body, the mean lifetime of ortho-positronium varies from approximately 1.8 ns in pure water to approximately 4 ns in human skin. 80 Moreover, both formation probability and mean lifetime depend on the concentration of the bio-fluids and bio-active molecules 81,82 and the mean lifetime can be established in the human body with the precision of approximately 20 ps. 29 There are investigations demonstrating differences between normal and cancerous cells with changes of the positronium lifetime during dynamic processes undergoing in model and living biological systems.…”
Section: Positronium Imagingmentioning
confidence: 99%
“…29 There are investigations demonstrating differences between normal and cancerous cells with changes of the positronium lifetime during dynamic processes undergoing in model and living biological systems. [79][80][81][85][86][87][88][89][90][91][92][93][94][95] Therefore, positronium may be used as a sensor of the surrounding tissue environment, and imaging of its properties inside the patient body may serve as additional diagnostic indicator. In general, positronium imaging can be defined as a method for the position-sensitive reconstruction of positronium properties (such as mean lifetime, formation probability, and 3g/2g rate ratio) within the imaged object.…”
Section: Positronium Imagingmentioning
confidence: 99%
“…An important advantage of this choice is also the availability of the reference sample—as a result of the hysterectomy, the entire organ is removed, and therefore both the changed (leiomyomas) and healthy tissues are available. Pilot studies made using the PALS technique 20 , 21 have already shown that the interpretation of o-Ps parameters will be possible if the result obtained for diseased tissue can be related to the results obtained for healthy tissue. Therefore, the samples are taken in pairs: abnormal and normal (neoplastic and healthy).…”
Section: Introductionmentioning
confidence: 99%
“…That is why they are radioresistant. Nevertheless, this effect is important when testing healthy and cancerous tissues of living organisms by the methods of positron annihilation spectroscopy [4].…”
Section: Introductionmentioning
confidence: 99%